2010
DOI: 10.1007/s00217-010-1272-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pure and mixed cultures of the main wine yeast species on grape must fermentations

Abstract: Mixed inoculation of non-Saccharomyces yeasts and S. cerevisiae are of interest for the wine industry for technological and sensory reasons. We have analysed how mixed inocula of the main non-Saccharomyces yeasts and S. cerevisiae affect fermentation performance, nitrogen consumption and volatile compound production in a natural Macabeo grape must. Sterile must was fermented in triplicates and under the following six conditions: 3 pure cultures of S. cerevisiae, Hanseniaspora uvarum and Candida zemplinina and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
115
3
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(137 citation statements)
references
References 42 publications
16
115
3
3
Order By: Relevance
“…In fact, among the beers, S. cerevisiae F12-7 pure culture consistently produced the highest amount of propanol (10,947.8 µg/L) and 2-methylpropanol (50,795 µg/L), while the mixed culture produced the highest amount of 3-methylbutanol (53,054.2 µg/L) and 2-phenylethanol (10,174.8 µg/L). However, these differed from the findings of others authors who observed an increase in alcohol formation in wines produced by mixed cultures, in contrast with those fermented with pure cultures of S. cerevisiae [30]. The differences in alcohol production from the various mixed-culture studies could probably be due to the use of different non-Saccharomyces yeasts or the degree of yeast succession.…”
Section: Volatile Compounds Of the Beerscontrasting
confidence: 93%
“…In fact, among the beers, S. cerevisiae F12-7 pure culture consistently produced the highest amount of propanol (10,947.8 µg/L) and 2-methylpropanol (50,795 µg/L), while the mixed culture produced the highest amount of 3-methylbutanol (53,054.2 µg/L) and 2-phenylethanol (10,174.8 µg/L). However, these differed from the findings of others authors who observed an increase in alcohol formation in wines produced by mixed cultures, in contrast with those fermented with pure cultures of S. cerevisiae [30]. The differences in alcohol production from the various mixed-culture studies could probably be due to the use of different non-Saccharomyces yeasts or the degree of yeast succession.…”
Section: Volatile Compounds Of the Beerscontrasting
confidence: 93%
“…In the last couple of years, a number of studies that have focused on the potential application of C. zemplinina in wine fermentations have been published (1,18,29,30), mainly due to its ethanol ) for different C. zemplinina strains inoculated with the same strain of S. cerevisiae (Tukey's test; P Ͻ 0.05). ‫,ء‬ ‫,ءء‬ ‫,ءءء‬ and NS indicate significance at P Ͻ 0.05, P Ͻ 0.01, and P Ͻ 0.001 and no significant difference, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…As shown, the possibility to reduce the acetic acid content is closely connected to the strain combination and the type of inoculation performed. Moreover, other chemical parameters, such as higher alcohols and acetaldehyde should be monitored, since it has been pointed out that C. zemplinina can contribute to a great extent to their increase or decrease, respectively (1,18). Since all of the data presented here were obtained from pasteurized must, more investigations are necessary to assess the ability of C. zemplinina to compete with the natural microbiota of grape musts and to confirm that the mechanism responsible for the acetic acid reduction is due to S. cerevisiae osmotic stress relief.…”
Section: Discussionmentioning
confidence: 99%
“…The use of non-Saccharomyces yeasts, together with S. cerevisiae, may improve the quality of wine and diversify wine flavour (21).…”
Section: Introductionmentioning
confidence: 99%